The Gnostic and Hellenistic Backgrounds of in 1 Corinthians 1-4 - Mihăilă, Corin (Perichoresis, 2019)
First Corinthians 1-4 discusses the concept of sophia or wisdom as a central theme. It seems to be both a worldly standard by which the Corinthians judged their teachers and a concept which Paul redefines in light of the cross. Over the last century, two major proposals have been put forth as an explanation for the background of sophia: Gnosticism and Hellenistic Jewish wisdom. Those who advance the hypothesis of Gnosticism behind the concept, correctly identify in these chapters words and terminology that are commonly associated with Gnosticism. However, the literary context of 1 Corinthians 1-4, as determinative of meaning for these words, suggests different meanings associated with the cross. Moreover, claiming Gnostic influence on the writing of 1 Corinthians is guilty of anachronism. The Hellenistic Jewish wisdom proposal is likewise based on alleged linguistic and conceptual parallelism with Philonic type wisdom. It is argued, among other things, that the Corinthians were taught such wisdom by Apollos. This argument, however cannot be sustained, when we look at Apollos’ ministry in light of the information we have in the New Testament. As a result, both Gnosticism and Hellenistic Jewish wisdom are not viable hypothesis for the background of sophia.